Influence of Diagnostic Method on Outcomes in Phase 3 Clinical Trials of Bezlotoxumab for the Prevention of Recurrent Clostridioides difficile Infection: A Post Hoc Analysis of MODIFY I/II. (3rd August 2019) - Wilcox, Mark H; Rahav, Galia; Dubberke, Erik R; Gabryelski, Lori; Davies, Kerrie; Berry, Claire; Eves, Karen; Ellison, Misoo C; Guris, Dalya; Dorr, Mary Beth
Abstract: Background: The optimum diagnostic test method for Clostridioides difficile infection (CDI) remains controversial due to variation in accuracy in identifying true CDI. This post hoc analysis examined the impact of CDI diagnostic testing methodology on efficacy outcomes in phase 3 MODIFY I/II trials. Methods: In MODIFY I/II (NCT01241552/NCT01513239), participants received bezlotoxumab (10 mg/kg) or placebo during anti-CDI treatment for primary/recurrent CDI (rCDI). Using MODIFY I/II pooled data, initial clinical cure (ICC) and rCDI were assessed in participants diagnosed at baseline using direct detection methods (enzyme immunoassay [EIA]/cell cytotoxicity assay [CCA]) or indirect methods to determine toxin-producing ability (toxin gene polymerase chain reaction [tgPCR]/toxigenic culture). Results: Of 1554 participants who received bezlotoxumab or placebo in MODIFY I/II, 781 (50.3%) and 773 (49.7%) were diagnosed by tgPCR/toxigenic culture and toxin EIA/CCA, respectively. Participants diagnosed by toxin EIA/CCA were more likely to be inpatients, older, and have severe CDI. In bezlotoxumab recipients, ICC rates were slightly higher in the toxin EIA/CCA subgroup (81.7%) vs tgPCR/toxigenic culture (78.4%). Bezlotoxumab significantly reduced the rCDI rate vs placebo in both subgroups; however, the magnitude of reduction was substantially larger in participants diagnosed by toxin EIA/CCA (relative difference, –46.6%) vs tgPCR/toxigenic culture (–29.1%). In bezlotoxumab recipients, the rCDI rate was lower in the toxin EIA/CCA subgroup (17.6%) vs tgPCR/toxigenic culture (23.6%; absolute difference, –6.0%; 95% confidence interval, –12.4 to 0.3; relative difference, –25.4%). Conclusions: Diagnostic tests that detect fecal C. difficile toxins are of fundamental importance to accurately diagnosing CDI, including in clinical trial design, ensuring that therapeutic efficacy is not underestimated. Abstract : In MODIFY I/II, bezlotoxumab had a substantially greater magnitude of reduction in recurrent CDI in participants diagnosed by toxin assay versus indirect methods to determine toxin-producing ability (toxin gene polymerase chain reaction/toxigenic culture), i.e. 46.6% versus 29.1% relative reduction, respectively.